Molecular Segmentation of the Spinal Trigeminal Nucleus in the Adult Mouse Brain - Isabel M. García-Guillén; Margaret Martínez-; Luis Puelles; Pilar Aroca; Faustino Marín (Frontiers Media S.A., 2021)
The trigeminal column is a hindbrain structure formed by second order sensory neurons that receive afferences from trigeminal primary (ganglionic) nerve fibers. Classical studies subdivide it into the principal sensory trigeminal nucleus located next to the pontine nerve root, and the spinal trigeminal nucleus which in turn consists of oral, interpolar and caudal subnuclei. On the other hand, according to the prosomeric model, this column would be subdivided into segmental units derived from respective rhombomeres. Experimental studies have mapped the principal sensory trigeminal nucleus to pontine rhombomeres (r) r2-r3 in the mouse. The spinal trigeminal nucleus emerges as a plurisegmental formation covering several rhombomeres (r4 to r11 in mice) across pontine, retropontine and medullary hindbrain regions. In the present work we reexamined the issue of rhombomeric vs. classical subdivisions of this column. To this end, we analyzed its subdivisions in an AZIN2-lacZ transgenic mouse, known as a reference model for hindbrain topography, together with transgenic reporter lines for trigeminal fibers. We screened as well for genes differentially expressed along the axial dimension of this structure in the adult and juvenile mouse brain. This analysis yielded genes from multiple functional families that display transverse domains fitting the mentioned rhombomeric map. The spinal trigeminal nucleus thus represents a plurisegmental structure with a series of distinct neuromeric units having unique combinatorial molecular profiles.